Impact of indocyanine green-fluorescence imaging on distal pancreatectomy with celiac axis resection combined with reconstruction of the left gastric artery. Issue 5 (May 2019) - Oba, Atsushi; Inoue, Yosuke; Sato, Takafumi; Ono, Yoshihiro; Mise, Yoshihiro; Ito, Hiromichi; Ishizawa, Takeaki; Takahashi, Yu; Saiura, Akio
Abstract: Background: We previously reported the usefulness of distal pancreatectomy with celiac axis resection (DP-CAR) with left gastric artery (LGA) reconstruction to prevent ischemic gastropathy. To evaluate the reconstruction quality, we performed intraoperative angiography with indocyanine green (ICG)-fluorescence imaging. Methods: 21 consecutive patients planned for DP-CAR with LGA reconstruction were enrolled in this prospective, exploratory single-arm study from 2014 to 2017. After LGA reconstruction, intraoperative angiography revealed continuous arterial flow passing through the anastomotic sites and gradually increasing tissue perfusion in the stomach. Results: Three patients were excluded. Among the remaining 18 patients, we obtained good flow in 11 patients and poor flow in 7 patients after initial LGA reconstruction. Among the seven patients with poor flow, five underwent LGA re-anastomosis, three recovered good flow. The incidence of grade B/C DGE was 14% (2/14) in the finally good flow group and 75% (3/4) in the poor flow group ( p = 0.019). Ischemic gastropathy occurred in two patients (50%) in the poor flow group ( p = 0.039), including one with a gastric perforation. Discussion: Our data show that intraoperative angiography with ICG-fluorescence imaging can evaluate the reconstruction quality, thus contributing to improvements in the short-term outcome of DP-CAR with LGA reconstruction.